2012
DOI: 10.1016/j.pbb.2012.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine reverses depressive-like behaviors and increases hippocampal acetylcholinesterase activity induced by olfactory bulbectomy

Abstract: The olfactory bulbectomy (OB) is an animal model of depression that results in behavioral, neurochemical and neuroendocrinological changes, features comparable to those seen in depressive patients. This study investigated OB-induced alterations in locomotor activity and exploratory behavior in the open-field test, self-care and motivational behavior in the splash test, hyperactivity in the novel object test and novel cage test, and the influence of chronic treatment with fluoxetine (10mg/kg, p.o., once daily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 65 publications
5
38
0
Order By: Relevance
“…Notably, OBX is known to cause retrograde degeneration of cholinergic neurons in the septum, thereby eliciting anterograde degeneration of cholinergic neurons from the septum to the hippocampus [57]. Numerous studies have reported that OBX induces a reduction in acetylcholinesterase and ChAT levels in the hippocampus in mice [58,59]. In the present study, 2 injections of MMI (75 mg/ kg, i.p.)…”
Section: Discussionmentioning
confidence: 84%
“…Notably, OBX is known to cause retrograde degeneration of cholinergic neurons in the septum, thereby eliciting anterograde degeneration of cholinergic neurons from the septum to the hippocampus [57]. Numerous studies have reported that OBX induces a reduction in acetylcholinesterase and ChAT levels in the hippocampus in mice [58,59]. In the present study, 2 injections of MMI (75 mg/ kg, i.p.)…”
Section: Discussionmentioning
confidence: 84%
“…OB has been characterised as inducing behavioural and neurochemical changes related to clinical depression, such as motor agitation, cognitive impairment, noradrenergic and serotoninergic dysfunctions [80]. Interestingly, it has been demonstrated that OB-induced depressive behaviour is reversed after chronic fluoxetine administration [81]. Furthermore, it was demonstrated that fluoxetine normalised OB-induced hyperactivity and that it reversed the physiological parameters associated with this model of depression, such as the altered heart rate and body temperature [82].…”
Section: Effect On Depressive-like Behaviourmentioning
confidence: 99%
“…After numerous preclinical studies demonstrated the efficacy of fluoxetine as a potent antidepressant [71][72][73][74]79,81], this compound was tested in patients suffering from depression. In one of the first human studies, the clinical efficacy and safety of fluoxetine was compared with imipramine in a double-blind, 5-week, parallel study performed on 40 depressed out-patients.…”
Section: A Reflection On the First Clinical Studies Validating The Anmentioning
confidence: 99%
“…An incision was made in the skin to expose the skull, and holes were drilled in both sides of the midline. The olfactory bulbs were then bilaterally sucked through a hypodermic needle (1.0-1.2 cm long with a rounded tip 0.80 to 1.2 mm in diameter) attached to a syringe (10 mL), with care used to avoid damaging the frontal cortex, as standardized by Machado et al (2012). Any bleeding was ceased and the holes were cleaned with gauze and covered with dental resin.…”
Section: Induction Of Depression By Obmentioning
confidence: 99%